Use of Library By the Students of Singhania University, Rajasthan: Exploring the Factors Influencing Library Usage among MA/M.Sc. Level Students at Singhania University, Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This study investigated the use of library bythe students of Singhania University , Rajasthan. The importance of library asan institution has been realized. The Objectives of this study were (a) toinvestigate the present use of library by the students of Singhania University, Rajasthan  (b)  to analyze  the  organizational  set up  of  library for  the purpose of effectivelearning (c) to identify the problems faced by the students  in the  use  of library  and  (d) to  give  recommendations  for effective use of library. The nature ofthis study was descriptive. The population of this study consisted of all theMA /M.Sc. level students. One hundred and eighty students of various programswere selected randomly as sample. A self developed questionnaire consisting of10 items was used as instrument for data collection. It was concluded that themajority of the students hesitated to use the library because of the problemsthey faced during its use. Lack of books, lack of organizational set up andlack of space and other physical facilities were the major factors associatedwith the less use of library